Pengaruh Lingkungan, Disiplin dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Pati Sari Di Aceh Tamiang - Syardiansah Syardiansah; Melati Putri Utami (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
This study aims to determine the effect of environment, discipline and work motivation on employee performance at PT. Pati Sari Desa Selamat Kec. Tenggulun Kab. Aceh Tamiang. The number of samples as respondents used was 119 people. For data analysis used multiple linear regression analysis, t test, f test and test the coefficient of determination adjusted (R2). From the regression results for this study obtained an equation that is Y = 2.265 + 0.048 X1 + 0.340 X2 + 0.115 X3. Partially the work environment does not have a significant effect on employee performance. Work discipline has a significant effect on employee performance. Work motivation has a significant effect on employee performance. Work environment, work discipline and work motivation simultaneously have a significant effect on employee performance